Partisipasi Masyarakat Dalam Proses Pembentukan UU Di Era Reformasi - Author: Saifudin (Jurnal Hukum IUS QUIA IUSTUM, 2006)
The establishment of Acts Ispart of state Aouthority, it shall be transparent, and account able. Italso needs public participation, thus, it will producea democratic Actand It will be benefical to the society. Furthemore, itis able to embodygoodgovernance  in accordance with the Constitution 1945.